Low power flexible monolayer MoS2 integrated circuits - Jian Tang; Qinqin Wang; Jinpeng Tian; Xiaomei Li; Na Li; Yalin Peng; Xiuzhen Li; Yanchong Zhao; Congli He; Shuyu Wu; Jiawei Li; Yutuo Guo; et al. (Nature Communications, 2023)
Abstract Monolayer molybdenum disulfide (ML-MoS2) is an emergent two-dimensional (2D) semiconductor holding potential for flexible integrated circuits (ICs). The most important demands for the application of such ML-MoS2 ICs are low power consumption and high performance. However, these are currently challenging to satisfy due to limitations in the material quality and device fabrication technology. In this work, we develop an ultra-thin high-κ dielectric/metal gate fabrication technique for the realization of thin film transistors based on high-quality wafer scale ML-MoS2 on both rigid and flexible substrates. The rigid devices can be operated in the deep-subthreshold regime with low power consumption and show negligible hysteresis, sharp subthreshold slope, high current density, and ultra-low leakage currents. Moreover, we realize fully functional large-scale flexible ICs operating at voltages below 1 V. Our process could represent a key step towards using energy-efficient flexible ML-MoS2 ICs in portable, wearable, and implantable electronics.